EFFECT OF SNOWBALL THROWING LEARNING MODEL ON STUDENTS' LEARNING OUTCOMES IN MATERIALS POWER TOOLS AND WORKSHOP EQUIPMENT BASIC AUTOMOTIVE WORK SUBJECTS IN CLASS XS MK N 1 BUNTOK ACADEMIC YEAR 2016/2017 - Denny Setiano (PARENTAS: Jurnal Mahasiswa Pendidikan Teknologi dan Kejuruan, 2018)
The difficulties faced by students in understanding the subject course of Power Tools and Workshop Equipment with conventional learning model can be seen from the student learning outcome which is still at below the KKM only 67 while the KKM setted by the school is 70. This study aims to determine whether there are differences in the effect of student learning outcomes between classes taught by Snowball Throwing and classes taught in Power Tools and Workshop Equipment of teaching class. The type of research used is True Experimental Design with Type of Pre-test and Pos-ttest Control Group Design. This research took sample random sampling and got result of class X TKR as experiment class with 25 students and class X TSM as control class with 25 students. Data collection using the test that is posttest in which data is collected then analyzed statistically. Based on post-test of data analysis, the mean value of the experimental class and control class are respectively 84 and 70. Based on the calculation of the difference between the average of experimental class and control class with a significant vaues of 5% obtained the price of ttable = 2.011 and from the calculation there is tcount = 2.30, then the result: tarithmetic = 2.30 > ttable = 2.011. This means that H0 is rejected and H1 is accepted. All in all, there is a difference in the effect of student learning outcomes between classes taught by Snowball Throwing and classes taught with lectures on Power Tools materials and Workshop Equipment at SMK N 1 Buntok.